EFEKTIVITAS PEMEKARAN NAGARI SUNGAI AUA KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Nurhida Hayani; Roni Ekha Putera; Hendri Koeswara (LPPM STISIP IMAM BONJOL, 2022)
Sungai Aua is one of the Nagari in Pasaman Barat Regency which has expanded Nagari Expansion against the background of problems in public service and uneven development. The Nagari Sungai Aua expansion was designed in 2016 and received a registration code as a Nagari Persiapan in 2017. The influence of the expansion of Nagari Sungai Aua has not been so visible and felt by the community as a whole, which is indicated by the fact that there are still some community groups who complain about the services in Nagari Sungai Aua and development that has not changed. Nagari Sungai Aua even though the expansion of Nagari Sungai Aua has been running for ± 5 years. This research was conducted using qualitative methods and descriptive approaches with data collection techniques through interviews, observation and documentation by used the theory of effectiveness according to Robert Duncan which consists of achieving goals, integration and adaptation. Research result shows that the expansion of Nagari Sungai Aua has been quite effective because it has fulfilled most of the indicators in the variables of Robert Duncan's theory of effectiveness. However, there are still some obstacles related to the delay in the Village registration code so that the indicators of the implementation period and the achievement of targets at the points of equitable development have not been met. Therefore, it is necessary to increase cooperation the Regional Government and the Central Government so that there is certainty regarding the Village registration code.